Improving outpatient care in adult inflammatory bowel disease: effect of implementation of a reminder checklist in the electronic health records (IBD-ERS)—a pilot study. Issue 1 (6th February 2023) - Bernasko, Nana; Venkateswaran, Niranjani; Coates, Matthew; Dalessio, Shannon; Williams, Emmanuelle; Clarke, Kofi
Abstract : Studies have shown that patients with inflammatory bowel disease (IBD) do not receive age appropriate preventive care services at the same rate as the general population. Providers extract information on preventive measures compliance by chart review, discussion with patients or deferment to primary care providers to ensure and document compliance. The aim of this pilot study was to evaluate the effectiveness of our standardised template which was incorporated in the electronic health records in order to provide the highest quality of clinical care and improve efficiency. We compared the outcomes before and after implementation of the template. In our preimplementation phase, we performed retrospective single-centre chart review of all patients diagnosed with IBD and treated with an immune modulator therapy between years January 2015–December 2016 and December 2019–July 2020. Preventive care measures included influenza and pneumonia, smoking cessation, checking thiopurine methyltransferase (TPMT) enzyme activity prior to starting thiopurines, screening for hepatitis B status, and tuberculosis (TB) testing prior to starting anti-TNF therapy. A total of 200 patients were included. Prior to the template implementation, manual extraction of data showed about 43% and 31% of the patients with IBD received influenza vaccination in 2015 and 2016, respectively. There were 40.9% who received pneumococcal vaccination, 57.5% with TPMT activity prior to thiopurine use, 60% had hepatitis B testing and only 12.5% had documented TB test. Post intervention, there was a significant increase in vaccination rates with 93.1% and 87.6% received influenza and pneumococcal vaccination, respectively (p<0.0005). About 94.7% had TPMT activity, 96.8% had hepatitis B and 98.9% had TB test completed (p<0.0005). The average time (minutes) to obtain information for each patient decreased from 12.27 to 4.62. Our study demonstrated a significant improvement in documented immunisation rates and quality of preventive care after implementation of standardised template.